METHOD OF EFFECTIVE USE OF INTERACTIVE METHODS AND DIDACTIC GAMES IN THE CULTIVATION OF THE LOGICAL THINKING OF ELEMENTARY SCHOOL STUDENTS (Academicia Globe: Inderscience Research, 2024)
This article discusses methods for the effective use of interactive methods and didactic games in the development of logical thinking of primary school students, types of methods, motivation for logical thinking.